Vaccinal Preventon of Anthrax in the Russian Federation and Its Immediate Prospects - A. N. Shevtsov; O. V. Korotyshev; S. A. Permyakov; I. P. Pogorelsky (Вестник войск РХБ защиты, 2023)
The purpose of the work is to show the possibilities of vaccine prophylaxis of anthrax in the Russian Federation and its immediate prospects. The article is dedicated to the vaccine preparations, available in Russia and abroad in the arsenal of medical remedies at present, to the history of their creation, to the effectiveness of their use and to the main directions of the improving of the vaccine prevention. The efforts to develop a new generation of vaccines are aimed mainly at the increasing of the safety of vaccines, reducing the frequency of their administration and improving their production technologies. The combined anthrax vaccine developed in the USSR can be used in the emergency prophylaxis of anthrax along with antibiotics. The development of vaccines based on immunogenic antigens synthesized by recombinant producers solves the problem of residual virulence and reactogenicity, as well as the problem of increasing stability and reduction of doses of modern anthrax vaccines. In the nearest future it is necessary: to develop an industrial technology of the production of anthrax vaccines based on recombinant strains – hyperproducers of protective antigen and include them in the prophylaxis and treatment regimens of anthrax infection; to develop scientific and methodological approaches and vaccines for mass immunization against anthrax; to evaluate the possibility of using new adjuvants for the construction of anthrax vaccines, more effective and safer than the existing ones.